Formazione, lavoro e tecnologia Nuove sfide e nuovi strumenti - Selmo, Laura (Pedagogia del lavoro, 2021)
Technology has radically changed the way we learn and work, and this fact opens new paths to explore and investigate. Some questions that guide us in this search are: What is the relationship between training, new technologies and work? What is the role of organizations in making workers learn and in supporting them to face the transformations? Starting from a theoretical and epistemological analysis of the relationship between training, technology and work, the book is focused on the description of the role of training in front of currently contests and on examination of some new methodological tools to develop learning and skills, as e-service-learning and design thinking. This book is aimed at HR trainers, HR consults and managers.